Tunneled island flaps in facial defects reconstruction - Miguel Pinto de Gouveia; Ana Isabel Gouveia; Ana Brinca; Ricardo Vieira (Sociedade Brasileira de Dermatologia, 2017)
Abstract The reconstruction of facial surgical defects is usually challenging for the dermatologic surgeon. Three different cases of facial defects in which tunneled island flaps were used are reported. In 2 cases, wide defects involving the nasal dorsum and ala were repaired using a nasolabial island flap tunneled through the lateral side of the nose. A tunneled island glabellar flap was used for medial canthus reconstruction in the third case. Despite complex pedicle dissection and frequent trapdoor deformation, tunneled island flaps allow reconstruction of wide defects in a single-staged procedure, camouflaging the scar of the donor area in boundaries of cosmetic units and preserving the facial central symmetry.